Development and Application of a LC-MS/MS Method for Simultaneous Quantification of Four First-Line Antituberculosis Drugs in Human Serum - Yunliang Zheng; Nana Xu; Xingjiang Hu; Qiao Zhang; Yanpeng Liu; Qingwei Zhao (Journal of Analytical Methods in Chemistry)
A simple, rapid, and sensitive liquid chromatography (LC)/mass spectrometry (MS) method was established and validated for simultaneous quantitation of pyrazinamide, isoniazid, rifampicin, and ethambutol in human blood sample. Samples were pretreated by a single-step precipitation with acetonitrile. Chromatographic separation was achieved on XSelecT HSS T3 column by gradient elution with a total run time of 5.0 min. MS detection was performed by a triple quadrupole tandem mass spectrometer in the multiple reaction monitoring mode with a positive electrospray ionization source. Isotope-labeled internal standard, especially rifampicin-D8, was applied to adjust for the loss during sample treatment. The established LC-MS/MS method showed a wide analytical range (pyrazinamide: 1.02∼60.0 μg/mL, isoniazid: 0.152∼10.0 μg/mL, rifampicin: 0.500∼30.0 μg/mL, and ethambutol: 0.0998∼5.99 μg/mL) and a good linearity (r > 0.99 for the four analytes) with acceptable accuracy and precision (90.15%∼104.62% and 94.00%∼104.02% for intra- and interaccuracy, respectively; RSD%: <12.46% and <6.43% for intra- and interprecision, respectively). It also showed excellent recoveries (79.24%∼94.16% for all analytes) and absence of significant matrix effect. This method was successfully applied to the quantification of four first-line antituberculosis (anti-TB) drugs, suggesting its suitability for therapeutic drug monitoring in the clinical practices.